Meritve sončnega sevanja v gozdu - Diaci, Jurij (Zbornik gozdarstva in lesarstva, 1999)
The know-how in the field of solar radiation distribution in forests is important for basic ecological investigations and silvicultural practice. Three methods of solar radiation assessment based on hemispherical canopy photography are compared in the present article: a hemispherical photography by means of a fish-eye lens, a horizontoscope and the ALI-2000 Plant Canopy Analyzer. Experiences, improved methods and a drawing of a horizontoscope stand which was elaborated at the Chair of Silviculture are presented. Fairly good results with some limitations can be achieved with the improved stable horizontoscope in silvicultural work. Hemispherical photography is appropriatefor the assessment of light conditions in all stand types and can thus be used in research work. The method has recently been undergoing intensive development. Digitalization of the entire system will speed up standardization. The ALI-2000 instrument is highly suitable for regeneration research in conditions of abundant plant vegetation, in reach sites and modified stands.
Keywords: gozdovi; merjenje; metode; sončno sevanje